MEASURING TEACHER WELFARE: A STUDY OF PROFESSIONAL DEVELOPMENT FACTORS - Feragi Azizun Putra (Penelitian dan Pengembangan Ilmu, 2025)
Teacher well-being is an essential factor in ensuring the quality of basic education. However, changes in education policy and the complexity of professional demands often lack adequate systemic support for teachers. This research aims to address the need for a more comprehensive understanding of teacher well-being, particularly in relation to professional development. The study focuses on four key aspects: the appropriateness of training programs, performance rewards, transparency in career development, and institutional support. This study adopted a qualitative descriptive approach. Data collection was conducted through a survey of 300 elementary school teachers, in-depth interviews with teachers, principals, and education officials, as well as documentation and administrative observations in the Talang Padang District. Thematic analysis was applied to identify patterns in teachers' perceptions of their well-being, which were then validated through triangulation between various data collection techniques and participants. The research findings revealed that most teachers considered the training programs provided to be less suited to classroom needs, career development mechanisms were less transparent, and administrative support from the government was very limited. The lack of teacher involvement in the policy planning and evaluation process also exacerbated the situation. The expected output of this study is the formation of a conceptual and empirical basis that supports the formulation of a more participatory teacher professional development policy, based on real needs, and capable of improving teacher welfare comprehensively, both economically and professionally.